ChemInform Abstract: Enantioselective NHC‐Catalyzed Formal [4 + 2] Cycloaddition of Alkylarylketenes with β, γ‐Unsaturated α‐Ketophosphonates. Issue 40 (12th September 2013) - Leckie, Stuart M.; Fallan, Charlene; Taylor, James E.; Brown, T. Bruce; Pryde, David; Lebl, Tomas; Slawin, Alexandra M. Z.; Smith, Andrew D.
Abstract A substrate‐depending diastereoselectivity is observed which provides predominantly the syn products from γ‐aryl α‐ketophosphonates of type (II) and (VII).